Public Health Impact of Pneumococcal Conjugate Vaccine in India: A Review of Available Evidence - Subhajit Chakraborty, (Public Health, 2026)
Pneumococcal disease is a major cause of morbidity and mortality in children less than five years of age with low- and middle-income countries having the highest incidences. It is caused by Streptococcus pneumoniae and it is presented as pneumonia, meningitis, sepsis, and otitis media, with pneumonia contributing a significant percentage of causes of childhood mortality that can be prevented. The pneumococcal disease burden in India is grossly disproportional as it has a large birth population, socioeconomic disparity, malnutrition, unpredictable exposure to environmental threats, and inconsistent access to quality healthcare. Although significant progress has been made in terms of child survival, pneumonia remains a significant cause of under-five mortality. India rolled out PCV in its Universal Immunization Programme in a phased way, where it started to introduce in high-burden states starting with the World Health Organization’s strong evidence and recommendations in 2017. The current narrative review is a synthesis of the available evidence from the published literature, surveillance reports, program evaluations, and modeling studies to determine the public health implications of PCV implementation in India. The review is concerned with the effectiveness of vaccines against pneumonia and invasive pneumococcal disease, child survival, economic effects, and difficulties in implementation. The available evidence suggests that PCV introduction in India has been connected to the decrease in severe and radiologically verified pneumonia hospitalization, decrease in the vaccine-type pneumococcal isolates, and possible indirect advantages because of herd protection. Averted cases, deaths, and healthcare expenses are modeled at a nationwide level to be substantial and have a scale-up type. PCV introduction is starting to deliver significant public health impact in India especially in reducing the morbidity associated with pneumonia. Financial permanence, enhanced surveillance and fair implementation are needed in order to maximize long term effects on child health and survival